EFEKTIFITAS PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN IBU TENTANG KANKER SERVIKS - Janu Purwono (AKPER Dharma Wacana, 2017)
The incidence of cancer increased from 12.7 million cases in 2008 to 14.1 million cases in 2012 or an increase of 12 percent. The number of cancer deaths worldwide in 2012 was found to be 8.2 million deaths. The prevalence of cancer in Indonesia is also quite high. The number of women of childbearing age who have not followed the early detection program of cervical cancer using IVA method. The purpose of this research is to know the effectiveness of health counseling to the knowledge of women of childbearing age about early detection of cervical cancer using Visual Acetic Acid Inspection method (IVA). The type of research is a comparative study conducted in Iringmulyo sub district. Metro Timur Kota Metro in October 2016. The population of this study is all mothers in awa mulyo village, amounting to 35 people. Analysis using paired sample t-test. Result of research got from 35 respondents show knowledge of respondent before giving counseling equal to 59,23 while knowledge after counseling is equal to 80,77 and result of t-test show show (p-value = 0,000 <0,05). Research indicates that counseling has proven to be effective in improving knowledge about early detection using IVA method.